Analysis of Mathematical Reasoning Ability and Mathematical Creative Thinking Elementary School Students in Solving Story Problems - Febriandi, Riduan; Herman, Tatang; Abidin, Zaenal; Farokhah, Laely (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
This research is motivated because the level of students' ability in solving story problems is still relatively low. So the objectives of this study are: (1) to determine the level of students' mathematical reasoning abilities from how to solve story problems; (2) to find out the misconceptions on each indicator of mathematical reasoning ability; (3) to determine the level of students' creative thinking ability on mathematical reasoning abilities. This study uses a descriptive qualitative method with the research subject being class V students, totaling 32 students at SD Negeri 58 Lubuk linggau for the Academic Year 2021/2022. The instruments used in data collection are test questions, observations, interviews and documentation. From the results of the study, it was found that the students' mathematical reasoning ability in solving story problems was 43.25% and students' creative thinking in solving story problems was 39.5%. From these results, students' creative thinking ability in solving story problems can be influenced by students' mathematical reasoning abilities. The conclusion is that students' mathematical reasoning and creative thinking skills in solving story problems are still relatively low.